Aplicação de escalonadores coexistentes para melhorar o desempenho de rede em máquinas virtuais - Dionysio, Stephany Zanchi (2016)
In a virtualized environment, time slice allocation should be based on virtual machines workloads requirements. However, the unpredictability of these workloads, combined with fair share nature of scheduling strategies, may impact the perceived quality of service of network I/O and CPU intensives virtual machines under server consolidation. This dissertation presents an in-depth analysis of quality of service variation under several scenarios, in order to assess this impact. Furthermore, a coexisting schedulers model, which aims to cluster virtual machines with similar workloads, is proposed as the main contribution of this research. The model validation argues that proper clustering based workload reduces the quality of service variation under server consolidation. In fact, the perceived quality of service under this model resemble a near native scenario.